Estudo epidemiológico retrospectivo do câncer infantojuvenil na região de Cascavel-PR por um período de 15 anos - Longo, Bruna Cristina (2020)
Childhood cancer (CC) is rare compared to adult cancer but represents the main cause of child death from disease in Brazil. It is treated by antineoplastic therapies, which target malignant cells, preferably those in the mitosis phase. However, oral mucosa cells are in a similar state which leads to unwanted manifestations, especially in children and adolescents. This retrospective epidemiological study evaluated medical records of patients up to 19 years-old treated at the Cascavel Cancer Hospital UOPECCAN from 2000 to 2014 and assessed those who were treated by dentist. The following informations were collected: gender, age, race, patient comorbidities, family history of cancer, home status, type of cancer, treatment, diagnosis metastases, relapses and patient status. Informations about clinical dental examination were also collected. Data were analyzed using descriptive statistics, chi-square and survival (Kaplan-Meier) tests. The male gender (55.22 %), 1 to 4 years age group (36.32 %), white people (87.06 %) and urban domicile (81.59 %) were the most prevalent. There was no report on family history of cancer in 95 cases (47.03%); 58.91% denied comorbidities. Leukemia was the most prevalent (35.83%), followed by lymphomas (14.42%) and renal tumors (8.46%). Metastasis was present in 16.41% and 22.38% have relapsed. Most of them underwent chemotherapy itself (50.25%) or combined with another therapy (40.30%). Chisquare test showed significance for patients >10 years with reticuloendothelial lymphomas/neoplasms (p=0.0003) and other malignant epithelial neoplasms/melanomas (p = 0.003); and at <10 years, with renal tumors (p=0.01) and neuroblastoma/other peripheral nerve cell tumors (p=0.01). These association were observed: patient's situation/metastasis (p=0.01), patient's situation/relapses (p=0.0004) and patient's situation/clinical staging (p=0.0004). Overall and disease-free survival (at 5 years) were, respectively, 70.3% and 71.63%. From 201 patients, only 100 were treated by dentist. Regarding dental examination, 86 (86%) presented oral manifestation, oral hygiene related alterations, infections and / or alterations related to mixed dentures. The most prevalent in each topic were respectively: mucositis (34%), gingivitis (9%), herpetic gingivalstomatitis (11%), caries (3%) and deciduous tooth exfoliation (8%). In conclusion, patients showed demographic profile like that of already reported in literature. Etiological factors were related to the geographic region. This study shows the importance of correct dental evaluation for prevention and treatment of patients with CC was evident, since changes in the oral cavity may compromise the patient systemic condition.